2022
DOI: 10.3390/jmmp6060131
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Near-Dry WEDM Process Variables through Taguchi-Based-GRA Approach on Performance Measures of Nitinol

Abstract: The machining of Nitinol shape memory alloys (SMA) through conventional machining techniques imposes several challenges due to the alloys’ comprehensive mechanical qualities. Wire electrical discharge machining (WEDM) process is a non-conventional machining technique that is suitable mainly for producing complex shape geometries with excellent surface features for difficult-to-cut materials. The current study attempted the use of a near-dry WEDM process for Nitinol SMA with the consideration of multiple respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The 95% CI was used to ensure the effect of the model terms. During this, a p-value lower than 0.05 implies that the corresponding term has some effect on the specified output measure [56,57].…”
Section: Anova Analysis For Response Measuresmentioning
confidence: 99%
“…The 95% CI was used to ensure the effect of the model terms. During this, a p-value lower than 0.05 implies that the corresponding term has some effect on the specified output measure [56,57].…”
Section: Anova Analysis For Response Measuresmentioning
confidence: 99%
“…They concluded that in an EDM process that mixes different powders into dielectric fluids, there is an increase in the efficiency in terms of an increase in the metal removal rate, a reduction in the tool wear, and an improved surface quality. Jay et al [29] performed a near-dry and low-dielectric-fluid WEDM process over nitinol SMA (nickel titanium alloy) using molybdenum wire as an electrode.…”
Section: Introductionmentioning
confidence: 99%
“…Powder mixed near-dry EDM outperformed conventional EDM in terms of tool wear, surface roughness, material removal rate, residual stress, and micro hardness [23]. Very recently, various dry and near-dry EDM experimental research studies were performed to improve the surface and machining speed using different gases, and gas-mist dielectric fluids [24][25][26].…”
Section: Introductionmentioning
confidence: 99%